A comparison of revascularization methods for peripheral arterial disease in diabetics: Changing trends in lower extremity revascularization from 2008 to 2014. (April 2022) - Qiu, Qiong; Stefanopoulos, Stavros; Kaissieh, Daniela; Wandtke, Meghan; Ren, Gang; Osman, Mohamed; Nazzal, Munier; Ahmed, Ayman
Objectives: This study examined the current demographic and outcome trends regarding endovascular and open revascularization for people with diabetes. Methods: The National Inpatient Sample database was utilized to identify diabetic patients who underwent lower extremity revascularization and amputation procedures between 2008 and 2014. International Classification of Diseases 9th edition codes were used to identify the procedures, diagnoses, and comorbidities. Results: We identified 38, 143 diabetic patients who underwent endovascular revascularization and 25, 415 who underwent open revascularization between 2008 and 2014. The number of endovascular and open revascularization procedures decreased steadily by 17.5% and 12.43% during the study period, respectively. The total charges for the endovascular procedure were greater than the open procedure (98, 761 vs. 80, 782, p ≤ 0.001) despite similar median length of stay (5 days (inner quartile range (IQR) = 1–10) vs. 5 days (IQR = 3–10), p ≤ 0.001). Compared to open, the in-patient amputation rate for endovascular patients has been increasing faster for both minor (11.75% vs. 0.37%) and major amputations (3.08% vs. 0.19%). Although the post-procedure amputation rates between endovascular and open procedures were increased for endovascular patients (odds ratio [OR] = 1.71, confidence interval [CI] = 1.35–2.18, p ≤ 0.001) in 2008, by 2014 the risk of major amputation was doubled in endovascular patients (OR = 2.88, CI = 2.27–3.64, p ≤ 0.001). African Americans were more likely to undergo minor amputation than Whites ( p ≤ 0.001). Lastly, diabetic patients with uncontrolled diabetes, systemic infection, weight loss, congestive heart failure, gangrene, and end-stage renal disease were more likely to undergo endovascular repair. Conclusions: As more medically complex patients undergo endovascular revascularization, endovascular revascularization for diabetic patients is becoming associated with higher total cost despite similar length of stay, minor amputation, and major amputation rates. Further studies are needed to continuously evaluate the post-procedural outcomes and cost effectiveness of this trend.